Prompt initiation of maintenance treatment following a COPD exacerbation: outcomes in a large insured population - Coutinho, Anna D (Int J Chron Obstruct Pulmon Dis, 2016)
BACKGROUND: The aim of this study was to extend previous findings and determine the value of prompt initiation of maintenance treatment (MT) following COPD exacerbations requiring hospitalization or an emergency department (ED) visit. PATIENTS AND METHODS: Administrative claims data (collected between January 1, 2009 and June 30, 2012) from an employer-sponsored commercially insured population were retrospectively used to identify patients with a COPD exacerbation resulting in hospitalization or an ED visit. Patients initiating approved MT for COPD within 30 days of discharge/diagnosis (prompt) were compared with those initiating MT within 31–180 days (delayed). COPD-related total, medical, and prescription drug costs during a 1-year follow-up period were evaluated using semilog ordinary least square regressions, controlling for baseline characteristics plus COPD-related costs from the previous year. The odds and number of subsequent COPD-related exacerbations during the follow-up were compared between the prompt and delayed cohorts using logistic regression and zero-inflated negative binomial models, respectively. RESULTS: A total of 6,521 patients with a COPD-related hospitalization or an ED visit were included, of whom 4,555 received prompt MT and 1,966 received delayed MT. Adjusted COPD-related total and medical costs were significantly lower for the prompt MT than the delayed MT cohorts (US$3,931 vs US$4,857 and US$2,327 vs US$3,087, respectively; both P<0.010), as were COPD-related prescription costs (US$1,526 vs US$1,683, P<0.010) during the 1-year follow-up period. Patients receiving delayed MT were 68% more likely to have a subsequent exacerbation requiring hospitalization and 80% more likely to have an exacerbation requiring an ED visit. CONCLUSION: Prompt initiation of MT following a COPD-related hospitalization or an ED visit was associated with a significant reduction in COPD-related costs and odds of exacerbation in the following year compared with delayed initiation.